KOMUNIKASI INTERPERSONAL PENGASUH DALAM MEMBENTUK SIKAP POSITIF ANAK DIDIK DIPANTI ASUHAN AISYIYAH PEKANBARU - Jogy Fadena Pane; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Interpersonal communication is an interaction that is very important in establishing a good relationship between the educator with students at the orphanage. Through interpersonal communication educator can educate and teach students to be better. The aim of this study is to explain how the educator role of interpersonal communication in shaping positive attitudes of students in orphanages and explain interpersonal relationships educator in shaping positive attitudes of the students at the orphanage.This study was conducted in Pekanbaru Aisyiyah Orphanage located at Jalan Ahmad Dahlan Pekanbaru. This study used a qualitative descriptive study describes and interprets the data. Informants in this study were caregivers, students, and leaders Orphanage using techniques purposiv. Data collection techniques using observation, interviews, and documentation.These results indicate the role of educator in the form of interpersonal communication positive attitude of the students in the Orphanage Aisyiyah Pekanbaru going well. Interpersonal communication between educator with children educated in orphanages instrumental in helping educator to educate and change attitudes of the students at the orphanage so that students in orphanages have the attitude and behavior is good or positive. Educator relationship interpersonal communication in shaping positive attitudes of students in the Orphanage Aisyiyah Pekanbaru also going well. Good interpersonal communication between educator with students forming a good relationship between the educator with the students so that the creation of comfort for students in orphanages so to facilitate educator to educate and nurture students to be better.Keywords: Interpersonal Communication, Interpersonal Communication Purposes, Characteristics And Role Of Interpersonal Communication, Interpersonal Relationship, Orphanages And Educator